1999
DOI: 10.1073/pnas.96.22.12798
|View full text |Cite
|
Sign up to set email alerts
|

Sustained in vivo cardiac protection by a rationally designed peptide that causes ɛ protein kinase C translocation

Abstract: Brief periods of cardiac ischemia trigger protection from subsequent prolonged ischemia (preconditioning). Protein kinase C (PKC) has been suggested to mediate preconditioning. Here, we describe an PKC-selective agonist octapeptide, receptor for activated C-kinase (RACK), derived from an PKC sequence homologous to its anchoring protein, RACK. Introduction of RACK into isolated cardiomyocytes, or its postnatal expression as a transgene in mouse hearts, increased PKC translocation and caused cardio-protection fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
301
2
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 340 publications
(319 citation statements)
references
References 39 publications
15
301
2
1
Order By: Relevance
“…Once the peptide crosses the cell membrane, the disulfide bond breaks, the peptide cargo is trapped in the cell, and the peptide carrier can be washed out. These studies already demonstrated that the peptides have highly selective effects; they inhibit or induce translocation of their corresponding isozymes but not that of others (Gray et al, 1997;Dorn et al, 1999). In addition, at concentrations up to ϳ10 M, the peptides or the carrier have no toxic effects on the cell.…”
Section: Peptide Preparation and Deliverymentioning
confidence: 93%
See 2 more Smart Citations
“…Once the peptide crosses the cell membrane, the disulfide bond breaks, the peptide cargo is trapped in the cell, and the peptide carrier can be washed out. These studies already demonstrated that the peptides have highly selective effects; they inhibit or induce translocation of their corresponding isozymes but not that of others (Gray et al, 1997;Dorn et al, 1999). In addition, at concentrations up to ϳ10 M, the peptides or the carrier have no toxic effects on the cell.…”
Section: Peptide Preparation and Deliverymentioning
confidence: 93%
“…Activation of PKC is associated with translocation from the soluble to the particulate fraction of cells (Kraft and Anderson, 1983;Dorn et al, 1999). Therefore, to confirm that IPC translocates ⑀PKC isozyme in hippocampal organotypic slices, the effect of IPC on subcellular localization of ⑀PKC isozyme was determined by cell fractionation and Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the a nity of pseudo-adaptor peptide is lower than that of the true binding-site on the adaptor, when the pseudo-adaptor peptide leaves the enzyme, the enzyme binds the adaptor (step 3). Using this approach, we have identi®ed isozymeselective activators, or pseudoRACKs, for bPKC and for ePKC (Dorn et al, 1999). For more details see the text and (Souroujon and Mochly- Peptides that induce binding of PKC isozyme to its RACK in the absence of second messenger generation were also identi®ed.…”
Section: Modulation Of Binding To Adaptor Proteinsð a Therapeutic Oppmentioning
confidence: 99%
“…For more details see the text and (Souroujon and Mochly- Peptides that induce binding of PKC isozyme to its RACK in the absence of second messenger generation were also identi®ed. These activator peptides, collectively termed pseudo-RACK peptides, are derived from a sequence in PKC that shares homology with its corresponding RACK (Dorn et al, 1999;Souroujon and Mochly-Rosen, 1998). However, there is a charge di erence between the pseudo-RACK sequence and the corresponding sequence of the PKC-binding site on RACK.…”
Section: Modulation Of Binding To Adaptor Proteinsð a Therapeutic Oppmentioning
confidence: 99%